1982
DOI: 10.1063/1.93034
|View full text |Cite
|
Sign up to set email alerts
|

Compensating impurity effect on epitaxial regrowth rate of amorphized Si

Abstract: The epitaxial regrowth of ion-implanted amorphous layers on 〈100〉 Si with partly compensated doping profiles of 11B, 75As, and 31P was studied. Single implants of these impurities are found to increase the regrowth rate at 475 and 500 °C. The compensated layers with equal concentrations of 11B and 31P or 11B and 75As show a strong decrease of the regrowth whereas for the layers with overlapping 75As and 31P profiles no compensation has been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…This can be attributed to an increase in the grain growth rate by the presence of solute atoms ͑n-and p-type͒. 32,33 Suni et al 32 hypothesized that the SPE growth rate is related to the concentration of charged vacancies residing in the crystal, where the vacancy concentration is determined by the position of the Fermi energy level, which in turn can be tailored by the doping concentration. Park et al 33 proposed a mechanism based on the solute-induced reduction of the bond strength, which facilitates the bond-breaking ͑formation͒ process, resulting in the thermal generation of dangling bonds at the crystalline/amorphous interface during recrystallization.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to an increase in the grain growth rate by the presence of solute atoms ͑n-and p-type͒. 32,33 Suni et al 32 hypothesized that the SPE growth rate is related to the concentration of charged vacancies residing in the crystal, where the vacancy concentration is determined by the position of the Fermi energy level, which in turn can be tailored by the doping concentration. Park et al 33 proposed a mechanism based on the solute-induced reduction of the bond strength, which facilitates the bond-breaking ͑formation͒ process, resulting in the thermal generation of dangling bonds at the crystalline/amorphous interface during recrystallization.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of impurities on the recrystallization rate of amorphous Si has been intensively investigated in the past. In a certain concentration range, electrically active elements like B and P are known to have an increasing effect [3,4,5] on the SPER (solid-phase epitaxial regrowth) rate whereas the elements C, N, and O can retard it [6]. The recrystallization behavior of silicon amorphized by implantation of Rb and Cs has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Suni et al,20 found that compensated layers with equal concentrations of B and P or B and As showed a strong decrease in the regrowth rate whereas for the layers with overlapping As and P profiles no compensation was found. According to this relationship, at low temperature U is approximately independent of ~g (impurity concentration).…”
Section: The Kinetics Of the Regrowth Processmentioning
confidence: 99%